Akuntansi Keberlanjutan: Konsep, Implementasi, dan Tantangan dalam Organisasi Nonprofit - Feri (Jurnal Ilmiah Raflesia Akuntansi, 2023)
Sustainability accounting has become an important aspect in the management of nonprofit organizations, considering its role in enhancing transparency, accountability, and social impact.This research aims to explore the concept of sustainability accounting, its implementation practices, and the challenges faced by nonprofit organizations in adopting this approach.Through a literature review of various previous studies, this research identifies the key principles in sustainability accounting and how nonprofit organizations apply them in reporting and decision-making.Additionally, this research analyzes the main constraints faced, including resource limitations, regulatory complexity, and the level of stakeholder awareness.The findings of this research are expected to provide insights for academics and practitioners in enhancing the effectiveness of sustainability accounting implementation in the nonprofit sector, as well as formulating strategies that can support the financial and operational sustainability of organizations.